To study the commercial and operational advantages and disadvantages of mega containerships - Wee, Davina Li Juan (2014)
It all started in the month of February in the year 2011, Maersk signed a contract with Daewoo Shipbuilding to order in 2 mega container vessels with expected delivery date on July 2013. They then went ahead soon after with the orders of a total of 20 mega container vessels of the same class. This has caused many industry players to speculate on the trends that could result with these mega container ships. Many experts have questioned the feasibility of the use of such mega vessels, there were mixed views. While some were sceptical of its benefits, others were both hands up in approval for it. One thing for sure is that it has made the container shipping market more competitive than before. Shippers have to follow suit in order to maintain their influence in the container shipping market. From the day the trend started, many studies have been done to determine the implications of the trends. Some even went further to speculate on the future of the container shipping market. This report brings you closer with an insight with key industry players and how they are coping or benefiting with the current mega trends. It also includes the actions taken by various port operators and how they are affected by these mega trends. Qualitative research has been done through various avenues to find out more about the truth behind these mega trends. Non-biased views and feedback have been taken into consideration by various parties in the container shipping industry to give an overall view. With the introduction of these mega vessels, the cascading effect occurs and it affects how the vessels are being deployed across various trade routes. This phenomenon has caused feeder and regional ports to be affected as well. These ports that once cater to smaller vessels are pressured to up their game plan by increasing their ability to cater to larger vessels. Lastly, the report will consolidate various predictions by key figures in the maritime industry on the outlook for the future of the container shipping market.